2015
DOI: 10.1515/eurodl-2015-0010
|View full text |Cite
|
Sign up to set email alerts
|

Research Trends in Turkish Distance Education: A Content Analysis of Dissertations, 1986-2014

Abstract: This paper presents a content analytic approach on doctoral dissertations in the field of distance education in Turkish Higher Education context from the years of 1986 through 2014. A total of 61 dissertations were examined to explore keywords, academic discipline, research areas, theoretical/conceptual frameworks, research designs, research models, tests and analyses, data collection tools, participants, variables/research interests, and leading contributor institutions. It is believed that this study can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 16 publications
3
28
0
10
Order By: Relevance
“…Similarly, Bozkurt et al (2015b) state that ignoring the use of theoretical or conceptual frameworks encourages researchers to report descriptive findings only. Anderson (2008) notes that theories allow researchers to make connections with other studies, provide deeper understanding of concepts, and facilitate the transformation of knowledge from one context to another.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Similarly, Bozkurt et al (2015b) state that ignoring the use of theoretical or conceptual frameworks encourages researchers to report descriptive findings only. Anderson (2008) notes that theories allow researchers to make connections with other studies, provide deeper understanding of concepts, and facilitate the transformation of knowledge from one context to another.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The most common parametric test is t-test. T-test is a widely applied test for many review studies (Bozkurt et al, 2015;Davies, Howell & Petrie, 2010). Regarding non-parametric tests, Wilcoxon test turns out to be used more frequently.…”
Section: Tests and Analysesmentioning
confidence: 99%
“…in various fields at the master's and doctoral levels, there are three ODL programs that offer master's (with and without thesis) and doctoral degrees (Kocdar & Karadag, 2015). Research trends in ODL in Turkey demonstrate that Anadolu University is the leading institution in terms of its contribution to ODL, where the specific focus has been on online learning processes (Bozkurt et al, 2015;Durak et al, 2017). In this context, it can be concluded that by investing in research and development, Anadolu University has contributed to the field of ODL by producing knowledge in an open university at scale, and by encouraging change and innovation for Turkish higher education.…”
Section: Learning Materials and Spacesmentioning
confidence: 99%